Influence of Substitution of Maize with Wheat Bran and Rice Bran in the Rations on Growth Performance and Nutrient Utilization in Local Pig (Zovawk) of Mizoram - Yendrembam, Mery Chanu; Samanta, Arup Kumar (Indian Journal of Animal Nutrition, 2018)
Twenty growing indigenous pigs (6-7 months of age) of Mizoram (Zovawk) of average body weights (22.07Â±1.15 kg) were randomly distributed into 4 groups of 5 animals each to study the effect of feeding wheat bran and rice bran based diet by replacing maize on growth performance and nutrient utilization. The animals in group G1 (control) were fed standard pig grower concentrate mixture (BIS, 1986) while in groups G2, G3 and G4, maize was replaced by wheat bran and deoiled rice bran (in equal proportion) at 60, 80 and 100% levels,respectively. During the feeding trial of 90 days, the average DM intake (g/head/day) was significantly higher (P